Risk factors for urinary tract infection in geriatric hip fracture patients: a systematic review and meta-analysis - Wang, Wei; Yao, Wei; Tang, Wanyun; Li, Yuhao; Sun, Hongbo; Ding, Wenbo (Frontiers in Medicine, 2024)
Background Urinary tract infection (UTI) is a prevalent and consequential complication in hip fracture patients, leading to significant disability and heightened healthcare expenditures. Consequently, there is a critical need for a comprehensive systematic review to identify risk factors and establish early and effective preventive measures. Methods A comprehensive search was performed across the PubMed, Cochrane, Embase, Web of Science, and Scopus databases (up to August 31, 2023). Article screening, data extraction, and quality assessment were independently completed by two reviewers. Results Forty-four studies were eligible for inclusion, yielding an overall incidence rate of 11% (95% CI: 8%−14%). Our pooled analysis revealed 18 significant risk factors, including being female (OR = 2.23, 95% CI: 1.89–2.63), advanced age (MD = 1.35, 95% CI: 0.04–2.66), obesity (OR = 1.21, 95% CI: 1.11–1.31), catheterization (OR = 3.8, 95% CI: 2.29–6.32), blood transfusion (OR = 1.39, 95% CI: 1.21–1.58), American Society of Anesthesiologists ≥III (OR = 1.28, 95% CI: 1.18–1.40), general anesthesia (OR = 1.26, 95% CI: 1.11–1.43), intertrochanteric fracture (OR = 1.25, 95% CI: 1.01–1.54), hemiarthroplasty (OR = 1.43, 95% CI: 1.19–1.69), prolonged length of hospital stay (MD = 1.44, 95% CI: 0.66–2.23), delirium (OR = 2.66, 95% CI: 2.05–3.47), dementia (OR = 1.82, 95% CI: 1.62–2.06), Parkinson's disease (OR = 1.53, 95% CI: 1.46–1.61), diabetes (OR = 1.27, 95% CI: 1.13–1.43), hypertension (OR = 1.14, 95% CI: 1.03–1.26), congestive heart failure (OR = 1.35, 95% CI: 1.10–1.66), history of sepsis (OR = 7.13, 95% CI: 5.51–9.22), and chronic steroid use (OR = 1.29, 95% CI: 1.06–1.57). Conclusion Our study identifies numerous risk factors strongly associated with UTI, offering compelling evidence and actionable strategies for improving clinical prediction, enabling early intervention, and facilitating targeted UTI management. Systematic review registration identifier [CRD42023459600], https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=459600.